PKM pemberdayaan ibu-ibu rumah tangga melalui pelatihan make up di Kabupaten Bantaeng - Rika Riwayani; Andi Nur Maida (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Training on empowering housewives through make up training in Bantaeng Regency is a partnership program to the community (PKM) as a solution to the problem of less productive housewives in Bantaeng Regency. The target audience for the training was 15 housewives in Bantaeng Regency. The training method is done in the form of lectures, questions and answers, discussions and practice. The PKM program aims to: 1) be more skilled in the cosmetology world. 2) develop the potential that has been owned for own commercial and own purposes. 3) increase productivity with makeup activities which of course can function for beauty and health. After conducting training through PKM research activities Empowering housewives through make up training in Bantaeng Regency, it can be concluded that: a total of 15 training participants have understood and understood well how to carry out makeup directly both for themselves and others. Furthermore, as many as 15 training participants were not only skilled in makeup but also inspired the importance of empowering housewives through ongoing makeup training.